Hubungan Body Image dan Frekuensi Konsumsi Makanan Cepat Saji Dengan Status Gizi pada Remaja Putri di SMA Batik 2 Surakarta - Shafira Azzahra; Sudrajah Warajati Kisnawaty; Dyah Intan Puspitasari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Adolescence is a critical stage of development, where nutrition and health influence the quality of individuals in adulthood.. Adolescent nutritional status is influenced by various factors such as body image and fast food consumption. The aim of this study was to determine the relationship between body image and the frequency of fast food consumption with nutritional status. This research employed a cross-sectional design involving 61 respondents selected through proportional random sampling. Body image was measured using the MBSRQ-AS questionnaire consisting of 33 items covering four aspects: appearance evaluation, body part satisfaction, fat anxiety, and body categorization. The frequency of fast food consumption was assessed using a FFQ, and nutritional status data were obtained through weight and height measurements using the BMI-for-age index. Data analysis was conducted using the Spearman Rank test to examine the relationship between body image and the frequency of fast food consumption with nutritional status. The results showed that the majority of female adolescents had a positive body image (55.7%) and rarely consumed fast food (60.7%), with most having a good nutritional status (78.7%). The Spearman Rank test indicated a significant relationship between body image and nutritional status (p < 0.001), while there was no significant relationship between the frequency of fast food consumption and nutritional status (p = 0.301). The conclusion of this study is that body image affects the nutritional status of female adolescents, whereas fast food consumption does not necessarily have a significant influence on nutritional status.